Crop-specific response of soil prokaryotic community to long-term intensification management: the importance of crop phase at sampling - Juan P. Frene; Silvina Bacigaluppo; Mariana Maury; Jimena Ortiz; Maximo Rivarola; Fernando Salvagiotti; Valeria Faggioli (Frontiers in Agronomy)
IntroductionThe ecosystem services provided by soil microbial communities are critical for the resilience of agroecosystems, ensuring environmental conservation and food security. Long-term experiments comparing contrasting crop rotations are valuable tools for monitoring microbial responses, but they rarely include all crop phases within a single year. Therefore, the long-term agronomic impact may be masked by the immediate effect of the crop evaluated. In this study, we compared different crop rotations based on the Intensification Sequence Index (ISI), which considers the soil occupation time, and analyzed the impact of cover crops and two nitrogen fertilization strategies.Material and methodsWe used an experiment initiated in 2006 with the following crop rotations: Soybean-Soybean, Maize-Wheat/Soybean, and Maize-Soybean-Wheat/Soybean. Soil samples were taken after the harvest of each summer crop phase (i.e., Soybean, Maize, Wheat/Soybean), and the soil prokaryotic community was monitored using 16S rRNA gene sequencing.Results and discussionWe observed that ISI and crop phase were the main predictors of microbial community composition, explaining 14.7% and 13.0% of the variation, respectively. Nitrogen fertilization had a minor effect (3.12%) and was detected only after maize sampling; cover crops had no significant effect. However, the presence of cover crops showed higher alpha diversity and an increased abundance of Proteobacteria. Maize enriched the abundance of certain taxa of Planctomycetes and Verrucomicrobia, while Soybean increased the abundance of Bacteroidetes and Proteobacteria. Comparatively, Soybean enriched Mucilaginibacter and Geobacter, while Wheat/Soybean enriched Brevundimonas and Roseimicrobium.ConclusionOur results demonstrate that crop phase is as important as the long-term legacy of crop rotations in shaping the microbial community and that specific taxa responses are highly dependent on the crop phase surveyed.